Increased Tumoral Microenvironmental pH Improves Cytotoxic Effect of Pharmacologic Ascorbic Acid in Castration-Resistant Prostate Cancer Cells - Li, Zhoulei; He, Peng; Luo, Ganhua; Shi, Xinchong; Yuan, Gang; Zhang, Bing; Seidl, Christof; Gewies, Andreas; Wang, Yue; Zou, Yuan; Long, Yali; Yue, Dianchao; et al. (Frontiers in Pharmacology, 2020)
Background: The anticancer potential of pharmacologic ascorbic acid (AA) has been detected in a number of cancer cells. However, in vivo study suggested a strongly reduced cytotoxic activity of AA. It was known that pH could be a critical influencing factor for multiple anti-cancer treatments. In this study, we explored the influence of pH on the cytotoxicity of ascorbic acid. We employed castration-resistant prostate cancer (CRPC) cell lines PC3 and DU145 to observe the therapeutic effect of AA on PCa cells that were cultured with different pH in vitro. We also observed the influence of pH and extracellular oxidation on cytotoxicity of AA in cancer cells using reactive oxygen species (ROS) assay, cellular uptake of AA and NADPH assay. Male BALB/c nude mice bearing prostate carcinoma xenografts (PC3 or DU145) were used to assess treatment response to AA with or without bicarbonate in vivo. The cellular uptake of AA in PCa xenografts was detected using positron emission tomography (PET). Small animal PET/CT scans were performed on mice after the administration of 6-deoxy-6-[18 F] fluoro-L-ascorbic acid ( 18 F-DFA).Our in vitro studies demonstrate that acidic pH attenuates the cytotoxic activity of pharmacologic ascorbic acid by inhibiting AA uptake in PCa cells. Additionally, we found that the cancer cell-selective toxicity of AA depends on ROS. In vivo, combination of AA and bicarbonate could provide a significant better therapeutic outcome in comparison with controls or AA single treated mice.18 F-DFA PET imaging illustrated that the treatment with NaHCO 3 could significantly increase the AA uptake in tumor. Conclusions: The alkalinity of tumor microenvironment plays an important role in anticancer efficiency of AA in CRPC.F-DFA PET/CT imaging could predict the therapeutic response of PCa animal model through illustration of tumoral uptake of AA.18 F-DFA might be a potential PET tracer in clinical diagnosis and treatment for CRPC.